Lean in [compact disc, unabridged] : women, work, and the will to lead - Sandberg, Sheryl (Random House Audio, 2013)
Sheryl Sandberg, Facebook COO has become one of America's most galvanizing leaders. In Lean In, she urges women to take risks and seek new challenges, to find work that they love, and to remain passionately engaged with it at the highest levels throughout their lives.